DECADAL ANALYSIS OF TEMPORAL VARIABILITY IN RAINFALL TRENDS IN OGBOMOSO - OlasunkanmiSuleman, Kamaldeen; LukmanAyobami, Sunmonu2; George, AtiladeÀlàgbé; Akeem, LawalSheu; Suliat, KemiRasaq (university of eloued -جامعة الوادي, 2022)
Ten-year (2009-2018) monthly rainfall data was obtained from the Nigerian Meteorological Agency (NIMET). The data was processed and analysed using OriginPro 8.5 software. Statistical tools such as standard deviation and Coefficient of Variation (CV) were used for data presentation while analyses were done using the Mann-Kendall and Sen’s slope of linear regression to examine variations across the months and years. Results revealed higher values around July and September while lower values were recorded around December and January. Seasonal variability shows a remarkable increasing trend with theexception of post-wet which recorded an insignificant downward trend. TheMann-Kendall and Sen’sslope estimator analyses revealedboth downward and upward trendsin rainfall the study period and the changes are strongly marked for certain years and less for others. This result would contribute significantly to the effective management and sustainable development of the social economic activities which are heavily rain-dependent, within the study area
ARTICLE
Keywords: Rainfall;Trend;variability;decadal;Mann-Kendall.